Synovial chondroma in Hoffa's fat pad: Case report and literature review of a rare disorder. (2017) - O'Connell, Lauren; Memon, Adeel R.; Foran, Paul; Leen, Eamon; Kenny, Patrick J.
Highlights: Synovial chrondroma is a rare condition of which the aetiology remains unclear. Large palpable lesions represent an atypical presentation. The diagnosis is often not immediately apparent. However it is usually suggested by radiologic investigation and confirmed on histology. Disease recurrence is not infrequent after excision (15–23%) and patients should be counselled regarding this. Malignant transformation whilst uncommon has been described. At present no definite criteria exist in order to make the diagnosis of malignancy. Due to the above risks of recurrence and malignancy, long term follow up of affected patients is advised. Abstract: Introduction: Synovial chrondomatosis is a rare disorder characterised by the development of hyaline cartilage from the synovial membrane. Large isolated lesions in the Hoffa's fat pad are an uncommon entity. Presentation of case: A 33 year old gentleman presented complaining of progressive knee pain associated with an enlarging lesion on the anterior aspect of the right knee, with associated locking and giving way. Examination revealed a firm 4 × 5 cm lesion adjacent to the patellar tendon. Subsequent CT and MRI demonstrated a lesion in the inferior aspect of Hoffa's fat pad, with a second lesion adjacent to the proximal tibiofibular joint, in addition to advanced degenerative changes and a meniscal tear. He proceeded to excisional biopsy. Histological analysis was consistent with a solitary synovial osteochondroma. There were no atypical features suggestive of malignancy. Discussion: Synovial chondromatosis is a rare disorder affecting the synovial joints. The underlying pathophysiology is thought to be metaplastic change of the synovium to hyaline cartilaginous tissue. Transformation to malignancy has been described but is uncommon with an estimated risk of 5%. It is 1.5–2 times as prevalent in males versus females. Symptoms which patients may complain of include pain;locking and giving way; and palpable masses. The management usually entails removal of the mass lesion with or without accompanying synovectomy. Recurrence of disease may occur in up to 15–23% of patients. Conclusion: Synovial chrondromatosis is a rare but well recognised condition. Long term follow up is advised in view of the risk of recurrence and malignant transformation.